the differences of intrapartum types to the risk of postpartum depression on primiparous mother in public hospital of yogyakarta municipality - riansih, chici; makiyah, sri nabawiyati nurul; kartini, farida (Universitas Respati Yogyakarta, 2019)
Postpartum depression is one of serious problems that women experience after giving birth. Depression symptoms found in postpartum mothers include sadness, anxiety, crying, temperament, lack of appetite, insomnia, and inattentive to the baby. It is a part of the symptoms of maternal psychological disorders that lead to the postpartum depression. This study used quantitative research with analytic observational research design. The population of primiparous postpartum mothers is 60 people consisting of 20 postpartum mothers of Sectio Caesarea, 20 spontaneous postpartum mothers, and 20 vacuum extraction postpartum mothers in the Public Hospital of Yogyakarta Municipality. The sampling teachnique used consecutive sampling. The study utilized Edinburgh Postnatal Depression Scale (EPDS) questionnaire. Bivariate analysis used ANOVA statistical test followed by post hoc test and Chi-Square test with 95% of confidence level. The results of the analysis show Respondents data who were at risk of postpartum depression in Sectio Caesarea intrapartum (16 or 80%) compared to vacuum extraction intrapartum (5 or 13%) and spontaneous intrapartum (7 or 35%). There was a difference on the type of Sectio Caesarea intrapartum with spontaneous intrapartum and vacuum extraction with the risk of postpartum depression of p-value = 0.001 (p <0.05). The difference of the risk was significant on the type of Sectio Caesarea intrapartum when compared with vacuum extraction and spontaneous intrapartum, while between vacuum extraction and spontaneous intrapartum was not significantly different. The conclusion of this study is that there are differences in the type of Sectio Caesarea intrapartum with spontaneous intrapartum and vacuum extraction on the risk of postpartum depression among primiparous mothers in Public Hospital of Yogyakarta Municipality.